2016
DOI: 10.3389/fpsyg.2016.00715
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Infant Familiarity and Novelty Responses to Words at Lexical Onset

Abstract: This study suggests that familiarity and novelty preferences in infant experimental tasks can in some instances be interpreted together as a single indicator of language advance. We provide evidence to support this idea based on our use of the auditory headturn preference paradigm to record responses to words likely to be either familiar or unfamiliar to infants. Fifty-nine 10-month-old infants were tested. The task elicited mixed preferences: familiarity (longer average looks to the words likely to be familia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 54 publications
4
18
0
Order By: Relevance
“…When a child first begins producing one consonant stably and consistently, as established by VMS identification, he or she is particularly attentive to that speech sound in input word forms (as shown in Majorano et al ., ). When the child has advanced to production at VMS level of more than a single consonant, the known (VMS) consonants no longer hold his or her attention; instead, the child seems to discover a world of varied stimuli and to begin to attend more to what is novel or unfamiliar (for further discussion see DePaolis, Keren‐Portnoy, & Vihman, ; Vihman et al ., ). This series of studies solidly establishes an effect of the child's own level of production of speech sounds on the way she processes or represents those sounds.…”
Section: The Relationship Of Emergent Vocal Production Skills To Speementioning
confidence: 99%
See 2 more Smart Citations
“…When a child first begins producing one consonant stably and consistently, as established by VMS identification, he or she is particularly attentive to that speech sound in input word forms (as shown in Majorano et al ., ). When the child has advanced to production at VMS level of more than a single consonant, the known (VMS) consonants no longer hold his or her attention; instead, the child seems to discover a world of varied stimuli and to begin to attend more to what is novel or unfamiliar (for further discussion see DePaolis, Keren‐Portnoy, & Vihman, ; Vihman et al ., ). This series of studies solidly establishes an effect of the child's own level of production of speech sounds on the way she processes or represents those sounds.…”
Section: The Relationship Of Emergent Vocal Production Skills To Speementioning
confidence: 99%
“…For example, DePaolis et al . () relate vocal production to word‐form recognition at 10 months; Horváth et al . () show, at 16 months, a correlation between reported expressive vocabulary size and novel word learning; and Fernald, Swingley, and Pinto () demonstrate that expressive vocabulary size, not age, is the best predictor of processing speed at 18 and 21 months.…”
Section: Learning Mechanisms: the Complementary Systems Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The infant's position along this continuum seems to be determined by a variety of factors related to the task and/or age (e.g., Aslin, 2007; Houston‐Price & Nakai, 2004; Hunter & Ames, 1988). However, it is frequently the case that the observed direction of preference does not conform with expectations based on these dimensions; the infancy literature is rife with examples of counterintuitive patterns of preference (e.g., Bosch & Sebastian‐Galles, 2001; Dawson & Gerken, 2009; DePaolis et al, 2016; Fiser & Aslin, 2001; Johnson et al, 2009; Jusczyk & Aslin, 1995; Sebastian‐Galles & Bosch, 2009; Thiessen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…If the infants or toddlers correctly perceived the number of syllables concerning the relevant word sounds, we expected that the amount of time they spent looking toward the ball stimuli would differ between the match and non-match conditions. A significant difference in looking time during two conditions (matched familiar and non-matched novel conditions) has been regarded as evidence that a child can distinguish between them, and thus, that they can correctly perceive the number of stimuli (Gerken et al, 2015;DePaolis et al, 2016). The condition during which the child spends more time looking at the stimuli is not clear: some studies have reported that familiar stimuli received more attention (i.e., longer looking time) from infants and toddlers during modality-matching in a visual-auditory setting (e.g., Starkey et al, 1983;Golinkoff et al, 1987), whereas other studies have reported that unexpected events received greater attention from infants (Mix et al, 1997;Kobayashi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%